2. \( \frac{-12 m^{6} n^{-4} p^{2}}{3 m^{2} n^{-6} p^{3}} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To simplify the expression \( \frac{-12 m^{6} n^{-4} p^{2}}{3 m^{2} n^{-6} p^{3}} \), you can start by dividing the coefficients and then simplifying each variable: 1. Divide the coefficients: \( \frac{-12}{3} = -4 \). 2. For \( m \): \( m^{6} \div m^{2} = m^{6-2} = m^{4} \). 3. For \( n \): \( n^{-4} \div n^{-6} = n^{-4 - (-6)} = n^{-4 + 6} = n^{2} \). 4. For \( p \): \( p^{2} \div p^{3} = p^{2 - 3} = p^{-1} \). Putting it all together, we have: \[ -4 m^{4} n^{2} p^{-1} = -\frac{4 m^{4} n^{2}}{p} \] So, the simplified form of the expression is \( -\frac{4 m^{4} n^{2}}{p} \).